Trends in a State Pharmaceutical Assistance Program for Low-income Older Adults in Wisconsin - Kevin Look; Nam Hyo Kim; Laura Dague; Aaron Winn (University of Minnesota Libraries Publishing, 2020)
Introduction: Many older adults face difficulty in affording their prescription drugs, despite having coverage available through Medicare Part D. SeniorCare is Wisconsin's pharmaceutical assistance program that provides comprehensive drug coverage for low-income older adults who are not eligible for full Medicaid benefits. Methods: We analyzed SeniorCare enrollment and pharmacy claims data from 2014 to 2018. Results: Total drug expenditures increased by 19.3%, with the proportion of expenditures paid by SeniorCare and members decreasing while the proportion paid by other payers increased. Specialty drugs accounted for a substantial and growing proportion of total expenditures (20.4% in 2018) despite accounting for <0.2% of all claims. Conclusions: Total drug expenditures in SeniorCare have steadily increased over time, primarily due to rising average expenditures per drug fill and increased use of specialty drugs. However, SeniorCare members have been largely protected from these increases and have paid a decreasing proportion of costs over time.   Article Type: Case Study